Histopathological Effects of Carbamazepine on The Reproductive System of Male Rats - HAYDER ALAA (Al-Qadisiyah Journal of Pure Science, 2021)
This research aims to identify the effect of carbamazepine on genital tissues of male rats.  In this experiment (20) male from adult rats were randomly assigned to 2 groups, Each group comprises (10) animals. Control group  gavage with distilled water, First group  gavage carbamazepine concentration (30) mg/kg of body weight. After 45 days, genitals eradicated for the purpose of textile on study them, Histological examination showed pathological changes in the occurrence of the testis in (T1) represented by its small diameter tubular deferens Also, the number of cells formed for sperm cells and spermatid and leydig cells has been reduced and cells for Spermatogonia get necrosis of the facility.